Costa Rica - Social Spending and the Poor - Ribe, Helena; Víquez, Roxana (World Bank, Washington, DC, 2012)
In social protection, Costa Rica has a well-established social assistance network to protect vulnerable groups, but it does not adequately reach the very poor. Costa Rica is not likely to be able to rely on favorable economic conditions to reverse these trends. Macroeconomic projections do not show signs of the consistent growth that characterized the past ten years, and which allowed the government to continue increasing investment in the social sectors. Relative to gross domestic product (GDP), Costa Rica already spends more on social services overall than other countries in Latin America, and considerably more than the average for other countries at similar stages of development outside the region. Moreover fiscal pressures will not only limit the government's ability to increase social spending, but could also act as a drag on real growth prospects for the economy as a whole. This underscores a key finding of the report: that social sector challenges cannot be resolved only through the allocation of more resources, but that they will require reforms which improve management and efficiency in the use of available resources. New instruments and approaches will be required that focus on obtaining value for money in the social programs.